Pengaruh Rancangan Acak Kelompok Lengkap (RAKL) Pada Pengaruh Harga Barang Dan Jasa (Studi Kasus: Pematang Siantar) - Sitorus, Yohana; Saragih, Sukma Dermawan; Simamora, Diana Syahputri; Berasa, Wahyuni Susi Sulastri (Interdisciplinary Explorations in Research Journal, 2024)
This study aims to analyze the effect of goods and services prices on inflation in North Sumatra using the Randomized Complete Block Design (RCBD) method. Inflation is an economic phenomenon influenced by various factors, including changes in the prices of goods and services. The data used in this research is inflation data from eight groups of goods and services classified by the Central Statistics Agency (BPS) of North Sumatra for the period from January to June 2023. The RCBD method is applied to determine the extent to which the prices of goods affect inflation within the designated groups. The analysis results show a significant influence of goods and services prices on the inflation rate. This research is expected to provide deeper insights into the factors influencing inflation and serve as a reference for further studies related to economic policy in North Sumatra.